Effect of HIPing and degassing on the low cycle fatigue behavior of A319 cast alloy. (21st August 2019) - Le, P W; Liu, X S; He, G Q; Ge, B; Weng, Z Z; Wang, Q G
Abstract: Microstructure and low-cycle fatigue (LCF) behavior of A319 cast alloy were investigated in this work. Microstructure analysis indicated that both degassing and hot isostatic pressing (HIPing) process could help to reduce and eliminate porosity. The strain-controlled low-cycle fatigue tests were conducted at total strain amplitude ranging from 0.2% to 0.4%. The stress-strain hysteresis loops were acquired and the effect of HIPing and degassing on cyclic deformation behavior was analyzed combining the cyclic stress response curves. Moreover, the effect of HIPing and degassing on LCF life was analyzed, and a fatigue life model based on the area fraction of defects was proposed which was found to be suitable to predict life. Finally, the fatigue fractography observation showed that the presence of porosity could accelerate the initiation and propagation of cracks and the fatigue failure of materials.